Asthma-associated prostate enlargement and bladder smooth muscle hypercontractility: unveiling a potential link to LUTS - Peibin Cen; Ming Chen; Xin Qiu; Wenbin Guo; Hongyu Lan; Xingyu Zhou; Ming Lei; Guohua Zeng; Qingfeng Yu (BMC Urology)
Abstract Background In male patients, benign prostate hyperplasia (BPH) and overactive bladder (OAB) secondary to BPH are the primary causes of Lower Urinary Tract Symptoms (LUTS). Recent clinical studies have reported an increased risk of LUTS, particularly severe LUTS conditions, in male asthmatic patients. However, the potential link and mechanism remain unclear. In this study, we investigated the structural and molecular characteristics of the prostate, and the structural and functional characteristics of the bladder in an asthma rat model. Methods An asthma model was induced in rats through the intraperitoneal injection of ovalbumin. Prostate and bladder tissue structure was examined with Hematoxylin and Eosin (H&E) and Masson’s trichrome (MT) staining, respectively. Prostatic smooth muscle contraction-related and synthesis-related protein levels were assessed using western blotting. Detrusor contractions were examined in an organ bath. Results Prostate epithelial thickness was significantly increased in asthmatic rats, accompanied by changes in molecular markers, including increased expression of desmin and tropomyosin and decreased expression of vimentin in the prostate tissue. The bladder wall structure and bladder weight were similar in both the asthma and control groups. Acetylcholine induced concentration-dependent bladder smooth muscle contractions, which were significantly enhanced in strips from asthmatic rats, however, acetyl-β-methylcholine and carbachol induced concentration-dependent bladder smooth muscle contractions were similar in both groups. Conclusions Our findings suggest a potential association between asthma and LUTS, with asthma possibly contributing to organ-specific changes, including prostate enlargement and increased smooth muscle contraction in the prostate and bladder. These results provide evidence for a biological connection between asthma and LUTS, laying a promising foundation for exploring new therapeutic strategies to manage LUTS in patients with asthma.